Dakwah Dan Radikalisme (Pendekatan Pemahaman Mitra Dakwah) - asmar, afidatul; Perdana, Dian Adi (Journal of Islamic Management, 2024)
Da'wah, as an effort to convey religious messages to society, is also a factor that can affect the level of radicalism in a society. Therefore, it is important to understand how the understanding approach of da'wah partners can contribute to reducing the potential for radicalism. This study aims to analyze the understanding approach of da'wah partners in the context of reducing radicalism. The method used is literature study and secondary data analysis. The results of this study indicate that the understanding approach of proselytizing partners can make a significant contribution in reducing radicalism. The understanding approach of proselytizing partners involves several important elements. First, it is important to understand the social, cultural, and political context in which da'wah is conducted. This helps da'wah partners to communicate religious messages in a way that is relevant and acceptable to the target community. Second, this approach also emphasizes the importance of a deep understanding of true and moderate religious teachings. The da'wah partner must have a strong knowledge of religious principles as well as the ability to explain them clearly and persuasively to the community.